2010
DOI: 10.1111/j.1468-005x.2009.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Is technological change really skill-biased? Evidence from the introduction of ICT on the Italian textile industry (1980-2000)

Abstract: This paper investigates the effects of the introduction of information and communication technologies (ICT) on the skills of a workforce.Using micro-data collected from workers in the textile sector, we analyse whether the introduction of ICT has modified workers' tasks, so that higher skills and longer training periods than before are necessary. Empirical evidence suggests that the adoption of ICT has no universal skill-biased effect for all occupations at least in the textile sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Computing skills: measures and returns Following the theory of skill-biased technical change, the Internet's rapid development and the emergence of new digital technologies at the end of the last century have encouraged the demand for workers with advanced computing skills. Such a change in the labour demand triggered a lively debate on the value of digital skills, in particular computing skills, and rising wage inequality between skilled and unskilled workers (Baccini and Cioni, 2010;Freeman, 2002;MacCrory et al, 2015).…”
Section: Skill-based Pay and Wage Differentialsmentioning
confidence: 99%
“…Computing skills: measures and returns Following the theory of skill-biased technical change, the Internet's rapid development and the emergence of new digital technologies at the end of the last century have encouraged the demand for workers with advanced computing skills. Such a change in the labour demand triggered a lively debate on the value of digital skills, in particular computing skills, and rising wage inequality between skilled and unskilled workers (Baccini and Cioni, 2010;Freeman, 2002;MacCrory et al, 2015).…”
Section: Skill-based Pay and Wage Differentialsmentioning
confidence: 99%
“…They were based on trade liberalization and international agreements that directly changed the global supply chain [8]. The restructuring of the T&A industry particularly affected the EU countries, such as Poland, which had to adapt the production profile to meet the market changes as well as technological and environmental conditions [9][10][11].…”
Section: Polandmentioning
confidence: 99%
“…Nevertheless, Baccini and Cioni () found that the introduction of ICTs in the textile industry has not modified tasks and increased the level of skills in all cases. These authors asserted that while some employees who use new technology succeed in increasing their skills, there continue to be employees who are not able to use these technologies and thus remain unchanged in their level of acquisition of such skills.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%